2012
DOI: 10.1088/1742-6596/407/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance analysis (BIA): a proposal for standardization of the classical method in adults

Abstract: Abstract:The accuracy of BIA measurements is limited by different sources of error such as physical model, cross sectional area, ethnicity, body hydration, age and level of body fat among other variables. Equation for each population is required as they can produce overestimation when manufacturer's equations are used. The classical measurements hand to foot has shown better correlation against hydrodensitometry than foot to foot or hand to hand. However there is a lack for an accepted standard of BIA procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…Although, the consumption of 1L of water did increase body mass it was not enough to statistically increase %FM. In this study, 1 kg difference in body mass is theoretically associated with a 0.68% higher FM which is in line with a previous study that suggests a non-voided bladder could affect BIA measurements by up to 1% [20]. Thus, non-voided bladder is likely to have minimal effects on %FM estimates.…”
Section: Discussionsupporting
confidence: 90%
“…Although, the consumption of 1L of water did increase body mass it was not enough to statistically increase %FM. In this study, 1 kg difference in body mass is theoretically associated with a 0.68% higher FM which is in line with a previous study that suggests a non-voided bladder could affect BIA measurements by up to 1% [20]. Thus, non-voided bladder is likely to have minimal effects on %FM estimates.…”
Section: Discussionsupporting
confidence: 90%
“…Above and beyond, the study of Slinde and Rossander-Hulthén [9] showed that not only the change of the measured impedance values lasts 2–4 h after each meal, but also during the day, the observed change is additive. However, González-Correa & Caicedo-Eraso [10], based on the study of Gonzalez et al [11], showed that conducting the measurement 2 h after a meal contributes to 2.9% of the measurement error only, which corresponds with the recommendations of Kyle et al [6], indicating the shorter periods of fasting as acceptable in clinical practice.…”
Section: Introductionmentioning
confidence: 82%
“…The main factors that may influence the results of body composition assessment are not only those factors that are included into equations to calculate the body composition, such as anthropometric measurements, gender, age, and ethnic group [33], but also the measurement procedure, used electrodes, and measurement errors [10,33]. However, for many additional factors, such as dietary intake of specific nutrients on the day leading up the day of measurement, the influence so far was not fully analyzed and precisely defined yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were in the supine position for exactly 5 min. All procedures were carried out according to the standardised procedures as outlined in Gonzalez-Correa & Caicedo-Eraso (2012). Previous experimental studies also used BIA as a measurement of fat mass and fat-free mass in individuals with ID (Salaun & Berthouze-Aranda 2012;Boer et al 2014) and DS (Mendonca et al 2011).…”
Section: Measurementsmentioning
confidence: 99%